Contesting Race and Citizenship : Youth Politics in the Black Mediterranean - Hawthorne, Camilla A.; Project Muse. (Ithaca [New York] : Cornell University Press, 2022)
"Drawing on ethnographic and archival research, this book explores the political mobilizations of Black Italians, the children of African and Afro-Latinx immigrants who were born and raised in Italy, as they engage with questions of citizenship, state racism, and global Black diasporic interconnection"--
Introduction : Contested Borders in the Time of Monsters -- Italian Ethnonationalism and the Limits of Citizenship -- Black Entrepreneurs and the "(Re)Making" of Italy -- Mediterraneanism, Africa, and the Borders of Italianness -- Translation and the Lived Geographies of the Black Mediterranean -- Refugees and Citizens-in-Waiting -- Conclusion : Looking South.
Description based on print version record.
Keywords: Racism -- Political aspects; Race relations -- Political aspects; Emigration and immigration -- Social aspects; Black people -- Social conditions; Black people -- Political activity; Italiens -- Identite ethnique; Racisme -- Aspect politique -- Italie; Noirs -- Activite politique -- Italie; Italians -- Race identity; Racism -- Political aspects -- Italy; Black people -- Italy -- Social conditions; Citizenship -- Political aspects -- Italy; Black people -- Political activity -- Italy; Italy; Italy -- Emigration and immigration -- Social aspects; Italy -- Race relations -- Political aspects; Electronic books